What Drives Economic Growth in some CEE Countries? - Simionescu, Mihaela (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2018)
Considering the potential factors that might generate economic growth, a target for any economy, this paper identified some determinants of economic growth in the countries from Central and Eastern Europe (CEE countries) that are member states of the European Union. The foreign direct investment was the most important determinant of economic growth in most of the countries (Bulgaria, Slovenia, Estonia, Hungary, Romania, Poland, Latvia, Lithuania) in the period 2003-2016, according to Bayesian bridge regressions. The indicators related to the level and the quality of labour resources proved to be insignificant in explaining the economic growth in these countries. Moreover, in Croatia, Estonia, Latvia, Lithuania, and Poland, the government expenditure on education had a negative effect on economic growth.